Library Promotion by Governance Institute of Home Affairs (GIHA) Library: An Overview - Rahmadanita, Annisa (Indonesian Journal of Librarianship, 2022)
Background: The ramifications of technological advancement is necessary for optimal operation of library and prompt provision of information. Purpose: This research aims to obtain an overview and analyze library promotion, as well as the development strategy carried out by the Governance Institute of Home Affairs (GIHA) Library. Method: It uses a qualitative method with data collection techniques in the form of interviews, observation, and documentation. Results: The results show an inconsistency in the promotion carried out by the GIHA Library. The promotion aspect of the library had been fulfilled, the Branding aspect contained digital library branding, and the IPDN library had utilized social media as a library promotion tool. However, in the copywriting aspect, the Customer Relationship Management aspect, the promotion roadmap and the design of library promotion programs have not been implemented properly. Conclusion: The library promotion implementation is not good enough. The development strategy that the GIHA Library can carry out is to increase the digital-based promotion. Keywords: Digital-Based Promotion, Library Promotion, University Library